Fabrication of a superhydrophobic poly(vinylidene fluoride) hollow fibre membrane by spray deposition. (1st February 2018) - Jin, Pengrui; Huang, Chuan; Li, Yifu; Li, Jiaxiang; Wang, Liao
Abstract : In this work, a poly(vinylidene fluoride) (PVDF) hollow fibre membrane for liquid–gas membrane contactor was coated with a superhydrophobic layer comprising a combination of hydrophobic SiO2 nanoparticles and polydimethylsiloxane. A rough layer of SiO2 deposited on the PVDF membrane resulted in an enhanced surface hydrophobicity. The surface structure of the pristine PVDF significantly affected the homogeneity of the generated SiO2 layer. A uniform surface coating on the PVDF upper layer resulted from the presence of micrometre and nanometre sized roughnesses on the surface of the PVDF membrane, which was achieved with a SiO2 concentration of 4.44 mg ml −1 (0.2 g/45 ml) in the coating solution. As a result, the water contact angle of the modified surface was recorded as 155 ± 3°, which is higher than that of the pristine surface.